Technical efficiency and its determinants in China's hog production - Xu TIAN; Fei-fei SUN; Ying-heng ZHOU (Journal of Integrative Agriculture)
China's hog production is undergoing a great transformation due to the soaring demand and changing raising system. Regarding the essential role of pork in Chinese diet, a systematic analysis on the productivity and efficiency of hog production can provide significant implications for policy makers. This paper investigates the productivity and efficiency of hog production and the determinants of technical efficiency in China using a household level panel data (2004–2010). A stochastic frontier translog production function with scaling property in inefficiency term is adopted for hog production analysis, and the determinants of technical efficiency are incorporated in a one-step estimation using maximum likelihood estimation. Our results show that the average technical efficiency of hog production in China is 0.5914. More importantly, we find that specialized farmers have higher technical efficiency than others, and technical efficiency in the eastern region is higher than that in Central and West China.